2016
DOI: 10.14238/pi56.2.2016.118-23
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of rotavirus diarrhea in Mataram, Lombok, Indonesia

Abstract: Background Rotavirus is the most common cause of severe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…20 A hospital based surveillance in Mataram (2010) revealed positive rate of 63.8%. 25 Similarly, a hospital based study in Riau (2015) reported detection rate of 62%. 31 During outbreak period in Lampung (2016 and 2018), positive rate of 74 samples collected from hospital and community was 74.3%.…”
Section: The Detection Rate Of Rotavirus Infection In Indonesiamentioning
confidence: 97%
See 2 more Smart Citations
“…20 A hospital based surveillance in Mataram (2010) revealed positive rate of 63.8%. 25 Similarly, a hospital based study in Riau (2015) reported detection rate of 62%. 31 During outbreak period in Lampung (2016 and 2018), positive rate of 74 samples collected from hospital and community was 74.3%.…”
Section: The Detection Rate Of Rotavirus Infection In Indonesiamentioning
confidence: 97%
“…The G genotypes of rotavirus found among children with rotavirus diarrhoea and their percentage in Indonesia during 2003-2018. Data generated from 18 studies, *: denotes the same origin of study (3 separated data from one study conducted by Nirwati et al, in the year of 2006, 2009, and 2010) 3,7,15,16,17,18,19,20,21,22,24,25,29,31,32,33,34,35.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RVA infection causes severe acute gastroenteritis among children and is responsible for approximately 60% of inpatients and 41% of outpatients in pediatric hospitals, respectively ( Nirwati et al, 2017 ; Utsumi et al, 2018 ). RVA is responsible for 2% mortality of all causes in children under 5 years old in Indonesia ( Parwata et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion, 55% in Asia, and 32% in Africa, of acute watery diarrhea hospitalizations and 28% of watery diarrhea deaths are due to rotavirus [3]. The Indonesian Rotavirus Surveillance Network (IRSN) conducted hospital-based surveillance studies across Indonesia from 1978 -2015 and found 38% -62% of watery diarrhea was caused by rotavirus [4], [5], [6], [7]. The estimated total direct medical costs of rotavirus outpatient and inpatient hospitalizations in Indonesia amount to US$16.7million per year [8].…”
Section: Introductionmentioning
confidence: 99%